Reconstructing Bhaskar's Transcendental Analysis of Experimental Activity - McWherter, Dustin (Cosmos and History: The Journal of Natural and Social Philosophy, 2012)
In this essay I attempt a thorough reconstruction and modification of Roy Bhaskar's "transcendental analysis of experimental activity" to show that this analysis contains a powerful critique of regularity theories of causal laws and a strong case for a transcendental realist, powers-based theory of causal laws.  Despite the short and scattered places in which this analysis occurs in Bhaskar's texts, my reconstruction synthesizes these textual resources to formulate a unified analysis of experimentation that derives three distinct conclusions from four presuppositions and a complex of transcendental arguments.  These conclusions are: 1) Extra-experimental reality is, to a significant extent, an open system, 2) Causal laws must be distinguished from constant conjunctions of events, and 3) Causal laws are the transcendentally real tendencies of generative mechanisms.